School Physical Education in the Service of Interdisciplinarity, in Significant Learning (Interdisciplinary Studies Journal, 2024)
This article presents the application of interdisciplinarity among the multiple dimensions of teaching work, based on the critical didactic-contextual analysis conducted in its educational practice. The goal is to answer whether interdisciplinarity between the curriculum components of Physics, Mathematics, and Physical Education enhances meaningful learning, allowing 160 first-year students of the New High School at the Garcitylzo do Lago e Silva Integrated School to share their ideas, actions, and reflections, motivating them to become active participants in their educational process. This study was approved by the CEP-UEA under the number: 5.608.528. Different curriculum components were applied: Physical Education in the form of Athletics - 100-meter race, long jump, high jump; Mathematics - linear functions, graphs; and Physics - velocity, acceleration, force, and friction – from the areas of knowledge of Languages and Their Technologies, Mathematics and Its Technologies, and Natural Sciences and Their Technologies. The analysis of calculations, measurements, marks in the athletics events (Physics), and graphs (Mathematics) highlights the learning outcomes from the interdisciplinary experience, which led to meaningful learning and challenged both teachers and students to become both subjects and objects of teaching and learning simultaneously.
Keywords: Physical Education; Physics; Math; interdisciplinarity